The Educational Strategy for Developing Reading Skills among a Sample of Fifth Grade Students with Specific Learning Disabilities - Ghonim, Wael Maher; Al-Laham, Haitham Ishaq; Al-Naqbi, Mona Mohammed (Journal of Curriculum and Teaching Methodology, 2025)
The current study aimed to identify educational strategies for improving reading skills among a sample of fifth-grade students with specific learning disabilities in reading. The study sample consisted of ten (10) students aged between 11 and 12 years, who were intentionally selected based on an official diagnosis of reading difficulties. The study adopted an experimental approach using a one-group pre-test–post-test design to verify the effect of the strategy on students’ reading fluency and reading comprehension abilities. A diagnostic reading skills test was used to measure improvement, in addition to implementing educational strategies that included repetition, modeling, and guided texts. The statistical analysis results, using the paired-sample t-test, showed that there were statistically significant differences at the 0.05 level between the students’ mean scores in reading fluency and reading comprehension before and after applying the strategy. The students’ post-test means were higher than their pre-test means after implementing the program. The study recommends the importance of employing this strategy during reading lessons to overcome the reading difficulties faced by students with specific learning disabilities, as well as providing the necessary training courses to implement it effectively in the classroom environment.
Keywords: Educational Strategies; Reading Skills Specific; Learning Disability